Pengaruh Keselamatan dan Kesehatan Kerja (K3) dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan CV Surya Kencana Food - Rizka Apriliyani (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to analyze the influence of occupational safety and health (K3) and work environment on the work productivity of employees CV Surya Kencana Food. This research is quantitative research using causal or causal approach. Data collection using research instruments, data analysis is statistical, with the intention to describe and test hypotheses. The population in this study was a permanent employee of CV Surya Kencana Food. The sample was determined by saturated sampling and obtained 57 respondents as samples. The results showed that: (1) occupational safety and health (K3) has no partial and significant effect on employee work productivity (2) the work environment has a partial and significant effect on employee work productivity (3) occupational safety and health (K3) and the work environment simultaneously affects employee work productivity. Keywords : Occupational Safety and Health (K3);Work Environment; Employee Work Productivity